The discourse of the river in the god of small things and the hungry tide - Jahan, Sumaya (2017)
The traditional human/nature dichotomy has long alienated humankind from nature and its preservation. The river is one such natural landscape. However, Rabindranath Tagore has found the river coupled with human interaction to be great source of inspiration for his literary works. With the example of Tagore’s approach to the river in mind, this essay explores the motif of the river in Arundhati Roy’s The God of Small Things (1997) and in Amitav Ghosh’s The Hungry Tide (2004). It argues that the river in the novels signifies more than just a nascent environmental monument that provides a spatial battleground to unravel the socio-political issues of class and environmental justice in the novel. I intend to explore how through questioning the romanticisation of the river by splitting the human/nature dichotomy, Ghosh and Roy engage deeply with the socio-political issues of class and environmental justice in India. Although the river is used as demarcation as narrative strategy, Roy and Ghosh show how environmental unconscious is cultivated in its protagonists through the sacralisation of the river as well the paradoxical love and danger it affects in the characters.